A Cybernetic Theory of Psychopathology. Issue 3 (3rd July 2018) - DeYoung, Colin G.; Krueger, Robert F.
Abstract: Cybernetics, the study of principles governing goal-directed, self-regulating systems, offers a useful approach to understanding psychopathology or psychological dysfunction, overcoming limitations of other naturalistic approaches. Whereas influential theories of psychopathology have relied on definitions of dysfunction rooted in evolution and fitness, we define psychopathology in terms of cybernetic dysfunction, failure to make progress toward important goals. Cybernetic function in organisms is not identical to evolutionary function, despite their causal phylogenetic relationship. We define psychopathology as persistent failure to move toward one's goals, due to failure to generate effective new goals, interpretations, or strategies when existing ones prove unsuccessful. This definition allows a thorough integration of dimensional approaches to psychopathology and personality and provides a new perspective on the nosology of mental disorder. We review evidence that the major dimensions of psychopathology correspond to major trait dimensions of personality, but we assert that extremity on these dimensions is neither necessary nor sufficient for psychopathology, which requires cybernetic dysfunction. Drawing from psychological and neurobiological research on personality and psychopathology, we present a theory of the mechanisms underlying the five major dimensions of psychopathology, some of their subdimensions, and the general risk factor for psychopathology. We conclude by discussing implications of our theory for research, diagnosis, and mental health interventions.